Implementation of a new third order weighted Runge-Kutta formula based on Centroidal Mean for solving stiff initial value problems - Amirtharaj, R. Gethsi Sharmila*; E.C. Henry (Recent Research in Science and Technology, 2011)
A new third order weighted Runge-Kutta formula based on Centroidal Mean(CeM) is derived and implemented. To illustrate the effectiveness of the method, a stiff problem has been chosen and compared with the classical fourth order Runge-Kutta method and the third order weightedÃ‚Â Runge-Kutta method based on Contraharmonic Mean(CoH). The stability of the new method is analysed. The investigation undertaken in the study reveals that the third order RK method based on CeM suits very well and indicates that this method is superior compared to the other methods discussed for the stiff initial value problems.